PENGARUH PERMAINAN SUSUN KATA TERHADAP KEMAMPUAN MEMBACA PEMULAAN SISWA DENGAN HAMBATAN INTELEKTUAL KELAS V DI SLB BANGUN PUTRA KASIHAN BANTUL - Hidayat, Luqman; Ayni, Anisa Aftur (JURNAL SKRIPTA, 2025)
Early reading skills are essential for students with intellectual disabilities as they influence their independence and academic development. However, many students with intellectual disabilities struggle with letter recognition, syllable formation, and understanding simple words. This study aims to determine the effect of the word arrangement game on early reading skills in fifth-grade students with intellectual disabilities at SLB Bangun Putra Kasihan Bantul. This study employs a quasi-experimental method with a one-group pretest-posttest design. The research sample consists of five students with intellectual disabilities selected through purposive sampling. The instrument used is an early reading test. Data were analyzed using descriptive statistics and the Wilcoxon test to assess differences in results before and after treatment. The findings indicate a significant improvement in students' early reading skills after intervention using the word arrangement game. This game helps students recognize letters, form words, and better understand word meanings. The study concludes that the word arrangement game is effective in enhancing early reading skills in students with intellectual disabilities. Therefore, this game can be an alternative method for teaching reading in special schools.